Antibodies against biotin‐labeled red blood cells can shorten posttransfusion survival. Issue 4 (11th March 2022) - Mock, Donald M.; Stowell, Sean R.; Franco, Robert S.; Kyosseva, Svetlana V.; Nalbant, Demet; Schmidt, Robert L.; Cress, Gretchen A.; Strauss, Ronald G.; Cancelas, José A.; von Goetz, Melissa; North, Anne K.; Widness, John A.
Abstract: Background: In hematologic and transfusion medicine research, measurement of red blood cell (RBC) in vivo kinetics must be safe and accurate. Recent reports indicate use of biotin‐labeled RBC (BioRBC) to determine red cell survival (RCS) offers substantial advantages over 51 Cr and other labeling methods. Occasional induction of BioRBC antibodies has been reported. Study Design and Methods: To investigate the causes and consequences of BioRBC immunization, we reexposed three previously immunized adults to BioRBC and evaluated the safety, antibody emergence, and RCS of BioRBC. Results: BioRBC re‐exposure caused an anamnestic increase of plasma BioRBC antibodies at 5–7 days; all were subclass IgG1 and neutralized by biotinylated albumin, thus indicating structural specificity for the biotin epitope. Concurrently, specific antibody binding to BioRBC was observed in each subject. As biotin label density increased, the proportion of BioRBC that bound increased antibody also increased; the latter was associated with proportional accelerated removal of BioRBC labeled at density 6 μg/mL. In contrast, only one of three subjects exhibited accelerated removal of BioRBC density 2 μg/mL. No adverse clinical or laboratory events were observed. Among three control subjects who did not develop BioRBC antibodies following initial BioRBC exposure, re‐exposure induced neither antibody emergence nor accelerated BioRBC removal. Discussion: We conclude re‐exposure of immunized subjects to BioRBC can induce anamnestic antibody response that can cause an underestimation of RCS. To minimize chances of antibody induction and underestimation of RCS, we recommend an initial BioRBC exposure volume of ≤10 mL and label densities of ≤18 μg/mL.